ANALISIS PENGARUH ENDORSER, KONTEN DIGITAL, DAYA TARIK PRODUK TERHADAP MINAT BELI ULANG PADA HIGHT DAN LOW INVOLVEMENT - Gusva Nanda Prayoga; Kussudyarsana Kussudyarsana (POLITEKNIK LP3I JAKARTA, 2025)
This research endeavors to examine the effects of endorsers, digital content, and product appeal on consumers' intentions to repurchase, incorporating product involvement as a moderating factor. A quantitative methodology was utilized, employing an online survey targeting 200 respondents who are active users of social media and have previously engaged in purchases via digital endorsements. The analysis of data was conducted through the Structural Equation Modeling Partial Least Squares (SEM–PLS) technique. The results indicate that each of the three independent variables endorser, digital content, and product appeal exerts a positive and statistically significant impact on repurchase intention. Furthermore, product involvement serves as a significant moderator within these dynamics, particularly affecting the relationships involving digital content and product appeal. The model produced an R² value of 0.797 and a Q² value of 0.794, demonstrating substantial predictive relevance in elucidating the dependent variable.